Managing the cervical spine in multiple myeloma patients. Issue 2 (15th November 2018) - Cawley, Derek T.; Butler, Joseph S.; Benton, Adam; Altaf, Farhaan; Rezajooi, Kia; Kyriakou, Charalampia; Selvadurai, Susanne; Molloy, Sean
Abstract: Discuss the relevant literature on surgical and nonsurgical treatments for multiple myeloma (MM) and their complementary effects on overall treatment. Existing surgical algorithms designed for neoplasia of the spine may not suit the management of spinal myeloma. Less than a fifth of metastatic, including myelomatous lesions, occur in the cervical spine but have a poorer prognosis and surgery in this area carries a higher morbidity. With the advances of chemotherapy, early access to radiotherapy, early orthosis management, and high definition imaging, including CT and MRI, surgical indications in MM have changed. Medical decompression (or oncolysis), including in the presence of neurological deficit and orthotic stabilization, are proving viable nonsurgical options to manage MM. A key to decision making is the assessment and monitoring of biomechanical spinal stability as part of a multidisciplinary approach.